De novo bone formation on macro/microporous silk and silk/nano-sized calcium phosphate scaffolds - Yan, Leping (2013)
Macro/micro porous silk/nano-sized calcium phosphate scaffolds (SC16) with bioactive and superior physicochemical properties have been recently developed. In this study, we aim at evaluating the new bone formation ability of the SC 16 scaffolds in vivo, using silk fibroin scaffolds (S16) as control. The CaP distribution profile in the scaffolds was characterized by Micro-Computed Tomography. The in vitro mineralization behavior was examined by immersion in Simulated Body Fluid solution from 1 to 14 days. The long-term hydration degree and weight loss ratio of the scaffolds were evaluated by immersion in an Isotonic Saline Solution from 1 month to 1 year. In vivo osteogenesis properties of the scaffolds were screened by implantation into the rat femur defects for 3 weeks. The results showed that the CaP phase distributed homogeneously in the SC16 scaffolds. Mineralization was only observed in SC16 scaffolds, and both scaffolds gradually degraded with time. The staining of the explants showed that new bone formation with higher density was observed in the SC16 scaffolds as compared to S16 scaffolds, guiding the growth of new bone directly onto its surface. These results demonstrated that the SC16 hybrid scaffolds are osteoconductive and can be good candidates for bone tissue engineering as promoted superior de novo bone formation.